Degradation of shores in the urban area of Irkutsk city under the influence of manmade reservoir - Kadetova, A. V.; Kozyreva, E. A.; Rybchenko, A. A. (Bulletin of the Geological Society of Greece, 2007)
The paper deals with the problems of destruction of the shores of the Irkutsk manmade reservoir (Russia). The object of study is the dam-abut area of the reservoir. The reason of peculiar attention given to the shore degradation is that the areas in question are located within the urban territory; the degradation can entail considerable social and economical harm. The investigation of factors influencing the shore scouring was based on the available information on the wind and wave action and the level conditions in the reservoir, as well as the data on the properties and state of grounds in the studied area. The investigation revealed that the water level variations and the ground properties are the main factors responsible for the shore degradation and preventing of its attenuation